DIP-COATING SENYAWA KALSIUM FOSFAT DARI BATU KAPUR BUKIT TUI DENGAN VARIASI RATIO MOL Ca/P MELALUI METODE SOL-GEL - Anggresani, Lia (IAIN Batusangkar, 2015)
Preparation of Dip-Coating Calcium Phosphate via sol-gel method using natural limestone Bukit Tui as calcium precursors and diammonium hydrogen phosphate as phosphorus precursors with various Ca/P mol ratio has been investigated. Etanol was used as solvent and DEA (dietanolamine) as stabilizing agent. Powder were prepared by calcinated the sol at 950oC. The results characterized by Fourier Transform Infra-red, X-Ray diffraction and Scanning Electron Microscopy. FTIR results showed that the vibration form was PO43-, P2O74-, O-H and CO2. X-Ray Diffraction (XRD) patterns of powder with various Ca/P mol ratio showed that the product of calcium phosphate was Ca2P2O7 and also found the hydroxyapatite Ca10(PO4)6(0H)2 in Ca/P ratio mol 1,7. Scanning Electron Microscopy (SEM) images of powder calcium phosphate revealed that their morphology were spheric and homogen. The coating process was done at glass substrate with coating speed 20 cm/min by calcinations at 400oC. . X-Ray Diffraction (XRD) patterns of thin layer showed that the product was Ca2P2O7 and Scanning Electron Microscopy (SEM) images of thin layer revealed that their morphology were bulk.Key words; natural limestone, calcium phosphate, hydroxyapatite, sol-gel, dip-coating